2017
DOI: 10.1113/jp274036
|View full text |Cite
|
Sign up to set email alerts
|

α‐Linolenic acid and exercise training independently, and additively, decrease blood pressure and prevent diastolic dysfunction in obese Zucker rats

Abstract: Although α-linolenic acid (ALA) and endurance exercise training independently attenuate hyperlipidaemia-related cardiovascular derangements, there is a paucity of information pertaining to their mechanisms of action and efficacy when combined as a preventative therapeutic approach. Therefore, we used obese Zucker rats to investigate the independent and combined effects of these interventions on cardiovascular disease. Specifically, animals were randomly assigned to one of the following groups: control diet-sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…Whole-body glucose tolerance and body mass in response to ALA and exercise We have previously reported in these same animals that ALA supplementation appropriately increased the ALA, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) contents of lipids within the blood and the liver, verifying the dietary intervention [41]. In the present study, we report that the consumption of ALA independently did not alter body weight throughout the experimental protocol (Fig.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Whole-body glucose tolerance and body mass in response to ALA and exercise We have previously reported in these same animals that ALA supplementation appropriately increased the ALA, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) contents of lipids within the blood and the liver, verifying the dietary intervention [41]. In the present study, we report that the consumption of ALA independently did not alter body weight throughout the experimental protocol (Fig.…”
Section: Resultssupporting
confidence: 82%
“…While the importance of adipose tissue for glucose homeostasis is well understood [2], it is unlikely that eWAT alone accounted for these findings in the ALA-Ex group as glucose tolerance was not different between ALA-Sed and CON-Sed animals despite a decrease in insulin signalling in the ALA-Sed animals. Indeed, recent work published from our lab found that insulin sensitivity in the liver was lower in the ALA-Ex compared with the CON-Ex group [41], and thus it is possible that the ability of insulin to suppress hepatic glucose output was also attenuated in the ALA-Ex group, which would explain the profound impact of the combined intervention on glucose tolerance in spite of increased skeletal muscle insulin sensitivity. Therefore, taken together, we provide clear evidence that ALA prevents exercised-induced improvements in wholebody glucose homeostasis in an obese rodent model, an effect that appears to involve, at least in part, alterations within eWAT.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Four-week-old male spontaneously hypertensive rats (SHRs) and age-matched normotensive Wistar-Kyoto (WKY) control rats were purchased from Vital River Laboratory (Beijing, China). The control diet (no.AIN-93G; 20% protein, 64% carbohydrate and 16% fat), LA-supplemented diet (no.AIN-93G + 10% safflower oil; 20% protein, 54% carbohydrate, and 26% fat) and ALA-supplemented diet (no.AIN-93G + 10% flaxseed oil; 20% protein, 54% carbohydrate and 26% fat;), as reported previously 13,14 , were obtained from Research Diets (New Brunswick, NJ). The animals were randomly divided into four groups with different diets for 8 weeks using a completely randomized design: (1) WKY: the normotensive WKYs fed with the control diet; (2) SHR: the SHRs fed with the control diet; (3) SHR + LA: the SHRs fed with LA-supplemented diet; (4) SHR + ALA: the SHRs fed with ALA-supplemented diet.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Protein carbonylation was assessed in left ventricle crude homogenates using the commercially available OxyBlot Oxidized Protein Detection Kit (catalogue no. S7150; Millipore, Billerica, MA, USA), as described previously (Barbeau et al 2017).…”
Section: Protein Carbonylationmentioning
confidence: 99%